2013
DOI: 10.4028/www.scientific.net/amr.788.283
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Pollution Analysis and Countermeasures of the Golf Course in Yangzonghai Area

Abstract: The golf course industry has become increasingly aware of potential problems related to pesticide and fertilizer movement from soil into surface water and groundwater . The objective of this study was to monitor and analysis the pollution level and scope, varying pattern, diffusion characteristics and the impact on the lake which are influenced by the Spring City Golf Course located in the catchment area of Yangzonghai Lake. It produced data on the quality of the surface water bodies, groundwater and soil envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Research on sustainability in golf has increased in recent years from the perspective of golf courses [15,[23][24][25][26][27][28]. Hence, there is a substantial literature on golf courses on their negative environmental impacts, especially with respect to excessive water use [29,30], environmental pollution [31], chemical inputs [32,33], and effects on wildlife and habitat [34,35].…”
Section: Research Model and Hypotheses Testingmentioning
confidence: 99%
“…Research on sustainability in golf has increased in recent years from the perspective of golf courses [15,[23][24][25][26][27][28]. Hence, there is a substantial literature on golf courses on their negative environmental impacts, especially with respect to excessive water use [29,30], environmental pollution [31], chemical inputs [32,33], and effects on wildlife and habitat [34,35].…”
Section: Research Model and Hypotheses Testingmentioning
confidence: 99%
“…This paper is conducted in the context of the golf tourism. In this sense, there is an extensive literature on golf courses and their negative environmental impacts, such as excessive water use, environmental pollution, chemical inputs and effects on wildlife and habitat [24][25][26][27]. However, as Minoli and Smith [28] affirm, golf courses have positive and negative environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [39] found that chlorothalonil and phosfolan-methyl from golf courses influenced the surrounding water environment greatly, chemical oxygen demand (COD cr ) reached a maximum concentration of 122 mg/L, and total nitrogen was up to 17.8 mg/L, exceeding the surface water environment quality standards of grade V in China. Haith [40] stated that five of the 37 pesticides resulted in potential acute risk to invertebrates and fish or algae when applied at label rates on lawns, fairways, or greens.…”
Section: Introductionmentioning
confidence: 99%